Pulmonary findings on high-resolution computed tomography in Takayasu arteritis. (16th February 2021) - Kong, Xiufang; Zhang, Jing; Lin, Jiang; Lv, Peng; Chen, Huiyong; Ji, Zongfei; Dai, Xiaomin; Jin, Xuejuan; Ma, Lili; Jiang, Lindi
Abstract: Objective: This study aimed to describe pulmonary high-resolution CT (HRCT) findings in Takayasu arteritis (TA) and to determine possible causes. Methods: A total of 243 TA patients were enrolled from a prospective cohort after excluding patients with other pulmonary disorders or incomplete data. Patients were divided into two groups: those with normal lung HRCT and those with abnormal lung HRCT. Clinical characteristics were compared between groups and binary logistic regression analysis was applied to identify possible causes of the lung lesions. Follow-up HRCT (obtained in 64 patients) was analysed to study changes in pulmonary lesions after treatment. Results: Of the 243 patients, 107 (44.0%) had normal lung HRCT while 136 (56.0%) had abnormal lung HRCT, including stripe opacity (60.3%), nodules (44.9%), patchy opacity (25.0%), pleural thickening (15.4%), pleural effusion (10.3%), ground-glass opacity (8.1%), pulmonary infarction (6.6%), mosaic attenuation (4.4%), bronchiectasis (3.7%) and pulmonary oedema (2.2%). Patients with abnormal HRCT were significantly more likely to have type II arterial involvement (25% vs 12.2 %, P  = 0.04), pulmonary arterial involvement (PAI; 21.3% vs 5.6 %, P  < 0.001), pulmonary hypertension (20.6% vs 8.4 %, P  = 0.01) and abnormal heart function (27.9% vs 7.6 %, P  < 0.001). Logistic regression analysis demonstrated that PAI, worsened heart function and age were associated with presence of pulmonary lesions. Pulmonary infarction, pleural effusion and patchy opacities improved partially after treatment. Conclusion: Pulmonary lesions are not rare in patients with TA. Age, PAI and worsened heart function are potential risk factors for presence of pulmonary lesions in TA.